2019
DOI: 10.1097/01.aoa.0000557657.79785.e6
|View full text |Cite
|
Sign up to set email alerts
|

Association of Paternal Age With Perinatal Outcomes Between 2007 and 2016 in the United States: Population-based Cohort Study

Abstract: (BMJ. 2018;363:k4372) As maternal age rises in the United States, the age of fathers is also increasing, with the percentage of births to fathers over age 40 doubling since the 1970s. While the effects of increased maternal age have been studied extensively, there is a lack of conclusive research regarding the effects of increased paternal age on pregnancy outcomes. There have been suggested links between the high number of male germ cell divisions in aging fathers and autism, genetic abnormalities a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 0 publications
1
17
0
Order By: Relevance
“…From 2004 to 2016, there was a decline in morbidity due to PE in China, while during 1980-2016, a yearly increase in morbidity was observed in the US (Fig. 1 and Table I) (10)(11)(12)(13)(14)(15)(16)(17)(18). These observations were in discordance with the previously determined higher incidence of PE in developing countries and led us to explore the reasons for this difference.…”
Section: Introductionmentioning
confidence: 70%
“…From 2004 to 2016, there was a decline in morbidity due to PE in China, while during 1980-2016, a yearly increase in morbidity was observed in the US (Fig. 1 and Table I) (10)(11)(12)(13)(14)(15)(16)(17)(18). These observations were in discordance with the previously determined higher incidence of PE in developing countries and led us to explore the reasons for this difference.…”
Section: Introductionmentioning
confidence: 70%
“…1,5 A recent population-based retrospective study of over 40 million births in the USA observed that a father's age ≥45 years increased the odds of gestational diabetes in the mother and preterm birth and neonatal seizures. 5 Earlier studies suggested advanced paternal age was associated with increased rates of pregnancy loss and poor obstetric outcomes. [6][7][8] A systematic review of adverse shortand long-term child outcomes showed an association between advancing paternal age and several neuropsychiatric disorders, as well as stillbirth, orofacial clefts and trisomy 21.…”
Section: Introductionmentioning
confidence: 99%
“…Increasing paternal age has been associated with an increase in the risk of adverse pregnancy outcome and may impact child health 1,5 . A recent population‐based retrospective study of over 40 million births in the USA observed that a father’s age ≥45 years increased the odds of gestational diabetes in the mother and preterm birth and neonatal seizures 5 . Earlier studies suggested advanced paternal age was associated with increased rates of pregnancy loss and poor obstetric outcomes 6–8 .…”
Section: Introductionmentioning
confidence: 99%
“…The medical literature tends to find that advanced paternal age is associated with worse birth outcomes, such as lower birth weight and higher risk of stillbirths (NyboAndersen and Urhoj, 2019, andKhandwala et al 2018). …”
mentioning
confidence: 99%